2009
DOI: 10.4315/0362-028x-72.8.1624
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Level of Escherichia coli O157:H7 in Feces and on Hides of Feedlot Steers Fed Diets with or without Wet Distillers Grains with Solubles

Abstract: The objective of this study was to determine if wet distillers grains with solubles (WDGS) from corn in diets affected Escherichia coli O157:H7 in growing and finishing cattle; steers (n = 603) were randomly assigned to diets with or without WDGS. Hide and fecal samples were collected monthly (October through June) from each animal for enumeration and enrichment of E. coli O157:H7. In the growing phase (0 or 13.9% WDGS diets), fecal prevalence for E. coli O157:H7 in steers fed a diet with WDGS was twice that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
54
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 25 publications
(19 reference statements)
8
54
3
Order By: Relevance
“…Our previous work indicated that E.Ăcoli O157:H7 prevalence in feedlot pen surface manure is reflective of E. coli O157:H7 fecal prevalence among cattle in the pen (Berry et al, 2010). Furthermore, this high degree of variation in pen prevalence is similar to that seen for pen fecal prevalence of E. coli O157:H7 in cattle in open-lot feedlots Smith et al, 2001;Wells et al, 2009). E. coli O157:H7 prevalence in the bedding/manure was higher during the hot months (table 4), which was likely due to the characteristic seasonality of prevalence of this pathogen in cattle.…”
Section: Generic E Coli and Prevalence Of E Coli O157:h7mentioning
confidence: 58%
“…Our previous work indicated that E.Ăcoli O157:H7 prevalence in feedlot pen surface manure is reflective of E. coli O157:H7 fecal prevalence among cattle in the pen (Berry et al, 2010). Furthermore, this high degree of variation in pen prevalence is similar to that seen for pen fecal prevalence of E. coli O157:H7 in cattle in open-lot feedlots Smith et al, 2001;Wells et al, 2009). E. coli O157:H7 prevalence in the bedding/manure was higher during the hot months (table 4), which was likely due to the characteristic seasonality of prevalence of this pathogen in cattle.…”
Section: Generic E Coli and Prevalence Of E Coli O157:h7mentioning
confidence: 58%
“…EHEC harbors SdiA, a regulator that senses AHLs and is necessary for efficient EHEC colonization of cattle; when AHLs are prominent within the bovine rumen, SdiA-AHL chemical signaling upregulated acid resistance genes to help EHEC pass through the acidic abomasum; AHLs are absent in other areas of the GI tract and lack of SdiA-AHL chemical signaling upregulates the LEE for efficient bacterial colonization of the recto-anal junction mucosa (Hughes et al, 2010). One study found association between seasonal prevalence and diet; fecal and hide prevalence of EC TRANSMISSION OF EHEC O157:H7 473 O157:H7 was higher in feedlot cattle fed wet distillers grains with solubles during periods of seasonally dependent low pathogen prevalence (Wells et al, 2009a). In a survey of five dairy farms in Argentina, prevalence of stx1 increased and stx2 decreased in the summer (Fernandez et al, 2009).…”
Section: Seasonal Prevalencementioning
confidence: 99%
“…Manure from animals fed distillers' grains has different physical, nutrient, and microbial characteristics from manure from animals fed traditional corn finishing diets (2), including higher dissolved and total phosphorus levels (11,13) and greater concentrations of some pathogenic bacteria (16,17). Numerous factors affect how fecal microorganisms are transported in manure-amended fields.…”
mentioning
confidence: 99%
“…1). It has been shown previously that the physical and microbial parameters of cattle manure can be influenced by diet (2,11,13,16,17) and that E. coli bacteria from different kinds of manure can have different transport characteristics in the laboratory (1). Although the differences were not statistically significant in this study, it was interesting that the transport percentages for fecal coliform, E. coli, and enterococcus bacteria in runoff were higher for plots receiving manure from corn-fed animals than from those receiving manure from distillers' grain-fed animals.…”
mentioning
confidence: 99%